Mechanical Properties of Cotton Stalk Micro Particles and Fibrillated Coir Fibre Reinforced Epoxy Composites - SENTHILKUMAR, T.; BHARIMALLA, A. K.; SUNDARAMOORTHY, C.; PATIL, P. G.; VIGNESHWARAN, N. (Cotton Research Journal, 2021)
The main aim of this study is to enhance the mechanical properties of epoxy composites by using agro residues. In this work, we have studied the mechanical behavior of epoxy composites reinforced with cotton stalk micro particles and fibrillated coir fibre. The cotton stalk was chipped and sieved to get the particle size range of 186 – 295 microns. The raw extracted coir fibre is coarser in nature with heterogeneous diameter and length. Hence, it was fibrillated in a conical refiner before using as reinforcing agent. The epoxy composite was prepared using three different reinforcements namely, 100% cotton stalk micro particles (CMP), 100% Fibrillated Coir Fibres (FCF) and 50:50 of CMP & FCF (MCF). The mechanical properties of composite samples were analyzed for tensile, flexural and impact strengths. MCF reinforced epoxy composites exhibited the highest tensile strength (34.18 N/mm2) and flexural strength (72.71 N/mm2). However, the impact strength was the highest in case of FCF reinforced composites (1.03 J/cm).